Cellulose Derivatives as Thermoresponsive Polymer: An Overview - Sonam Jain, Premjeet Singh Sandhu, Reetesh Malvi, Babita Gupta (Journal of Applied Pharmaceutical Science, 2013)
Cellulose is a linear homopolymer polysaccharide having water insoluble property. Various cellulose derivative prepared by etherification gains water solubility and shows thermoresponsive gelation. Thermoresponsive polymers are sensitive to thermal environment surrounding them and in response to it they show change in their property. Thermogelation behaviour of cellulose derivatives varies with degree and type of substitution. The main aim behind presenting this article is to summarize the thermosensitive property and application of various cellulose derivatives. This review stresses mainly on cellulose derivatives, methyl cellulose, hydroxypropyl methylcellulose and ethyl (hydroxyethyl) cellulose.
Keywords: Cellulose, Cellulose ether, Thermoresponsive polymer, MC, HPMC, EHEC.